Women and employment changing lives and new challenges / edited by Jacqueline Scott, Shirley Dex, Heather Joshi. - Dex, Shirley; Joshi, Heather; Scott, Jacqueline L. (Edward Elgar Publishing Limited, 2008)
Examines twenty five years of change in women's employment and addresses the challenges facing women. This book tackles issues including gender inequalities and ethnic diversities, and confronts such questions as what work-life balance means? It draws out the policy lessons that could improve economic and social well-being.